2007
DOI: 10.1111/j.1365-277x.2007.00751.x
|View full text |Cite
|
Sign up to set email alerts
|

Government advice on peanut avoidance during pregnancy – is it followed correctly and what is the impact on sensitization?

Abstract: The majority of mothers in this cohort avoided peanut consumption during pregnancy. It is likely that either the government advice is misunderstood by mothers, or that those who communicate the advice have not fully explained who it is targeted at.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 12 publications
1
34
0
Order By: Relevance
“…Evidence from two studies (2,19) designed to evaluate the impact of the 1998 COT recommendations found that there appears to be confusion among the general public regarding the COT recommendations and that the advice has not been interpreted as intended. More than 60 % of women reported having reduced (rather than avoided) consumption of peanuts during pregnancy and lactation, including those not targeted by the COT recommendations.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Evidence from two studies (2,19) designed to evaluate the impact of the 1998 COT recommendations found that there appears to be confusion among the general public regarding the COT recommendations and that the advice has not been interpreted as intended. More than 60 % of women reported having reduced (rather than avoided) consumption of peanuts during pregnancy and lactation, including those not targeted by the COT recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…There was also no indication that the target group (women with a family history of allergy) were more likely to take up the advice. Of children who developed peanut sensitisation or allergy, a significant number (77 % sensitisation, 40 % allergy) of mothers reported that they reduced their intake or avoided peanuts (19) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations